Estimation the levels of two genes expression and their effects on tetracycline resistance of Acinetobacter baumannii isolated from different sources - SUAAD ABID FAZAA AL-MIYAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Al-Miyah SAF. 2023. Estimation the levels of two genes expression and their effects on tetracycline resistance of Acinetobacter baumannii isolated from different sources. Biodiversitas 24: 176-181. Acinetobacter baumannii can cause severe infections of the blood, brain, and lungs. It may also results in infections of the urinary tract and wounds. It can be found on the skin, in food, drink, or soil, and can be transferred by direct contact. The pathogen Acinetobacter baumannii spreads quickly. This study aimed to find a relationship between the infection with Acinetobacter baumannii and the corresponding IL-17 level in patients' sera. To determine the effect of tetracycline exposure on the gene expression levels of the TetA and AdeB genes. This study included 150 samples from different patients suffering from burns, wounds, blood, and sputum. Samples have been tested by Vitek for the presence of Acinetobacter baumannii. Each isolate was then cultured on two separate Mueller-Hinton Agar (MHA) dishes, one with and one without tetracycline. RNA was extracted from all the cultured dishes and converted to cDNA. Quantitative real-time polymerase chain reaction (qRT-PCR) has then been done to evaluate the gene expression level of the TetA and AdeB genes and normalized to the results of the 16sRNA gene. The results of gene expression showed that isolates grown with tetracycline in the medium had significantly higher gene expression than isolates grown without the antibiotic for both the TetA (2.49 vs. 1.023, respectively) and AdeB (5.051 vs. 1.023, respectively) genes. The results of IL-17 showed a higher level in infected patients (21.37 pg/mL) compared to non-infected subjects (14.76 pg/mL).